Avaliação dos efeitos induzidos pelo nitrato de acetato de 4 - nitrooxibutila (NHPR1) sobre o sistema cardiovascular de ratos normotensos - Barbosa, Camila de Castro (2019)
Systemic arterial hypertension (SAH) is related to endothelial dysfunction attributed mainly by the reduction of nitric oxide (NO) bioavailability in the vascular wall and increased oxidative stress, resulting in chronic and abnormal increase in peripheral vascular resistance. Thus, it is characterized by high blood pressure levels, resulting in a change in vascular tone, where NO is the main endothelium-derived relaxing factor (EDRF). Nitric oxide plays a key role in the control and regulation of blood pressure through its influence on peripheral vascular resistance and vascular tone. Problems related to NO bioavailability are prime factors for the development, progression and maintenance of hypertension. The use of compounds that increase the bioavailability of NO has been a therapeutic strategy for the treatment of cardiovascular disorders for decades. Thus, the objective of the present study is to evaluate the effect of 4 - nitrooxybutyl acetate nitrate (NHPR1) on the cardiovascular system of normotensive rats. From the biological prediction, NHPR1 showed a vasodilating effect where the NO donor mechanism (Pa 0.849) was identified using the cutoff line Pa> 0.7 Pi = 0.000. In ex vivo tests, in isolated cranial mesenteric artery rings pre-contracted with FEN (1μΜ), NHPR1 was able to induce vasorelaxant effect in both functional endothelial rings (Emax = 100.0 ± 6.116, n = 10). in rings where the endothelium was removed (Emax = 100.0 ± 11.47, n = 7). After an electromechanical contraction with KCl (60 mM), NHPR1 showed no altered vasorelaxant response (Emax = 132.7 ± 7.103, n = 7). To assess the participation of the NO / GCs pathway was used ODQ (10 µM), a selective inhibitor of the soluble guanylate cyclase enzyme, which attenuated the vasorelaxant response to NHPR1 (Emax = 99.24 ± 7.338, n = 8). When performing non-selective blockade of potassium channels with ASD (3 mM), the vasorelaxant response of NHPR1 was not altered (Emax = 118.1 ± 4.828, n = 13). In the tolerance test, nitrate showed alteration in its induced response, which observed the occurrence of shift of the curve to the right, suggesting that there is the development of tolerance in the vasorelaxant response of NHPR1. In the evaluation of toxicity, oral administration of NHPR1 (300 and 2000 mg / kg) did not promote changes in body weight and organ weight, as well as food and water consumption compared to the control group. Acute administration of NHPR1 (1, 5, 10, 20, 50 mg / kg, iv) induced hypotension in normotensive animals (-4.06 ± 1.01; -6.18 ± 1.25; -15.39 ± 0.65, -11.71, ± 3.04, -17.19 ± 1.99 mmHg, respectively) and bradycardia (6.48 ± 3.64; 62.61 ± 12.88; 48.21 ± 9 , 08; 76.31 ± 13.44; 103.75 ± 12.13 bmp) in a dose - dependent manner. Thus, the vasorelaxant response promoted by NHPR1 possibly occurred due to its vasodilating effect involving NO release and subsequent activation of the NO-GCs-PKG pathway. This mechanism of action may be contributing to the hypotension and bradycardia observed in normotensive animals.